Inter Simple Sequence Repeat molecular markers to reveal the genetic diversity of superior durian of Gunungpati, Semarang, Indonesia - Evy Nasrika; Amin Retnoningsih (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nasrika E, Retnonongsih A. 2021. Inter Simple Sequence Repeat molecular markers to reveal the genetic diversity of superior durian of Gunungpati, Semarang, Indonesia. Biodiversitas 22: 4054-4059. Kalimantan is the center of many tropical fruits, including durian. One of the edible durians and favorited by many is Durio zibethinus, which has many superior varieties. Almost all regions in Indonesia have superior durian varieties; for example, superior durian Gunungpati from Gunungpati Sub-district, the center for producing durian in Semarang City, Central Java, Indonesia. ISSR analysis was carried out to reveal the genetic diversity of the superior durian Gunungpati. DNA isolation of 16 superior durians used the modified CTAB method. The genomic DNA was amplified using 10 ISSR primers and then electrophoresed using 2% agarose gel. Data were analyzed using NTSYS PC version 2.02. The resulting allele has a relative size of 220 bp-1800 bp, with 87.9% are polymorphic. The similarity coefficient of 16 varieties was ranged between 0.54-0.88. All the superior durian varieties examined were different accessions so that each variety has the potential to be registered as a new variety of superior Indonesian durian. Specific alleles are found in G1, G3, G7, G8, and G13, which can be an identity of these varieties.